"How will I know?" engagement with information resources: A comparison of undergraduates at Indiana and Kuwait Universities. Issue 4 (4th July 2016) - Al-Muomen, Nujoud; Shaw, Debora; Courtney, Michael
Abstract : Purpose: This paper aims to compare how undergraduates in Kuwait and Indiana Universities assess information resources for class assignments. Design/methodology/approach: Social science majors at Kuwait University and Indiana University Bloomington completed the Project Information Literacy survey. Findings: The students are comparable in how often they ask instructors or classmates for advice, but Kuwaitis are more likely to ask other people for assistance. Kuwaiti students generally are less critical in their evaluation of both library-based and web information resources but are more likely to consider librarian recommendations. Research limitations/implications: Institution-specific factors that were not specifically addressed include the following: the survey was administered online in Indiana and on paper in Kuwait, and the types of course assignments and/or students' information literacy instruction may also vary by institution. Practical implications: Librarians should continue to present information clearly and use a variety of instructional methods so that material is accessible. Librarian recommendations and modeling of evaluative behavior can assist international students. Social media may be useful in working with these students' more collaborative approach to assessing resources. Originality/value: The work updates the 2010 Project Information Literacy survey on undergraduates' evaluation of information resources for coursework. It also extends that survey to identify how students from Kuwait are different than USA undergraduates.